The Complexity of Work for Women who are HIV Positive: A Case Study in DKI Jakarta - Andi Nur Faizah (Yayasan Jurnal Perempuan, 2018)
The phenomenon of HIV-AIDS transmission places women in a difficult situation. The loss of family members such as husbands due to AIDS leaves women living with HIV positive in a struggle to access sources of livelihood. The condition of themselves as PLWHA, concerns about being stigmatized, caring for family members, and earning a living are the burdens of life they have to face. In this regard, this paper explores the complexity of the work of HIV-positive women. This study uses a qualitative method with a feminist perspective to get a complete picture of the livelihood of HIV-positive women. Based on interviews with five HIV-positive women, the findings found a link between social, identity, and gender categories that affect their livelihoods. HIV-positive women also transform themselves into their “normal” self by pretending to be healthy, able to work, have quality, and be independent. This is done as a form of resistance to the stigma attached to PLWHA.